Children’s perception of outdoor play in early childhood institutions: the Mosaic approach - Ribarić, Lana (Rethinking childhood II: child and space, 2026)
This paper had two main goals. The first was to determine if the preschool grounds of an early preschool institution can be viewed through Green´s (2013) theory of “special places” for children to play. The second goal was to determine how the participants would react to natural materials, loose parts, and collections of objects with a specific property. To answer the first research question, the Mosaic approach was employed as a participatory method that enables children to express how they view and use the interior and exterior of the preschool they attend. The method of observation was used to answer the second research question. Results based on the research on a convenient sample of children from one preschool class show that different spaces in the preschool grounds have different roles: the swings are used for swinging, the window of the small house that is a part of the slide is a bed, the benches are used for sitting, the slide is used for riding down the chute and hiding, sandboxes, the earth, and the grass are places to play, and dig. Trees hold a special place in the children’s play, serving as sites for exploring insects, climbing, jumping, and hiding. The collections of loose parts prepared for the children by the researcher enriched children’s play. This paper can be used as an example for preschool teachers who want to know more about how children from their class perceive the indoor and outdoor environment of the preschool. It can also be used by those teachers who wish to enrich children’s play by using a collection of loose parts.